High-resolution naturalness mapping can support conservation policy objectives and identify locations for strongly protected areas in France - Jonathan Carruthers-Jones; Adrien Guetté; Steve Carver; Thierry Lefebvre; Daniel Vallauri; Laure Debeir; Toby Aykroyd; Christian Barthod; Pascal Cavallin; Sophie Vallée; Fabienne Benest; Erwan Cherel; et al. (Communications Earth & Environment)
Abstract Intact natural landscapes are essential to both biodiversity conservation efforts and human well-being but are increasingly threatened and lack sufficient protection. Bold National and International protected area targets aim to address this problem, yet the question remains – where will these areas be located? Using France as a case study, we present a high-resolution method to map naturalness potential. The resulting map, CARTNAT, performs well at identifying areas which have already been recognised as worthy of strong protection, under both National and International designations, however, only 1% of the top 10% of high naturalness areas in France are currently strongly protected. CARTNAT is already being used to highlight potential sites for new protected areas supporting the French National Strategy for Protected Areas to 2030. We argue that spatially informed participatory decision making of this type has the potential to deliver on national and international protected area policy objectives.